2019
DOI: 10.1063/1.5111328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tab location relative to the nozzle exit on the shock structure of a supersonic jet

Abstract: This paper presents an experimental study of a Mach 2.0 jet manipulated using rectangular tabs to understand the mixing enhancement at the overexpanded and perfectly expanded state of the jet. This paper also compares the mixing effectiveness of the tabs in comparison with the fluidic injection reported in our previous work [Kumar et al., “Empirical scaling analysis of supersonic jet control using steady fluidic injection,” Phys. Fluids 31(5), 056107 (2018)]. Tabs used in this investigation were rectangular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Focusing the aspect ratio of the nozzle and nozzle pressure ratio (NPR) with the Mach number variation, the elliptic jet control with limiting tab [43] was investigated and showed that each parameter is important to control the jet flows, similar to the overexpanded plug nozzle jet [44] controlled by the passive method. Additionally, some researchers used ventilated triangular tabs to control the jet [45], control the supersonic elliptic jet with ventilated tabs [46], and to measure the impact of the tab location relative to the nozzle exit on the shock structure of a supersonic jet [47]. Khan et al [48] experimentally investigated the effect of the extended cowl on the flow field of planar plug nozzles for two different Mach number ranges (1.8 and 2.2) to observe the influence of the cowl length for the pressure distribution.…”
Section: Jet Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing the aspect ratio of the nozzle and nozzle pressure ratio (NPR) with the Mach number variation, the elliptic jet control with limiting tab [43] was investigated and showed that each parameter is important to control the jet flows, similar to the overexpanded plug nozzle jet [44] controlled by the passive method. Additionally, some researchers used ventilated triangular tabs to control the jet [45], control the supersonic elliptic jet with ventilated tabs [46], and to measure the impact of the tab location relative to the nozzle exit on the shock structure of a supersonic jet [47]. Khan et al [48] experimentally investigated the effect of the extended cowl on the flow field of planar plug nozzles for two different Mach number ranges (1.8 and 2.2) to observe the influence of the cowl length for the pressure distribution.…”
Section: Jet Controlmentioning
confidence: 99%
“…the jet flows, similar to the overexpanded plug nozzle jet [44] controlled by the passive method. Additionally, some researchers used ventilated triangular tabs to control the jet [45], control the supersonic elliptic jet with ventilated tabs [46], and to measure the impact of the tab location relative to the nozzle exit on the shock structure of a supersonic jet [47].…”
Section: Jet Controlmentioning
confidence: 99%
“…Semicircular corrugations tab shows 90% reduction in core length in comparison with uncorrugated tabs for higher nozzle pressure ratio (NPR). All the above mentioned authors examined the profile modification, whereas Arun Kumar et al (2019) found that the correct position to place the tab against the nozzle exit is first shock crossover point. Subsequently, a paper by Quadros et al (2021) investigated the effect of shape modification on rectangular tabs.…”
Section: Introductionmentioning
confidence: 99%
“…The stream is also affected by the azimuthal orientation of the vortex generator. The shock cell structure variation due to the positioning of the tab was studied by Arun Kumar et al (2019) and identified three flow categories according to the tab position. The categories of flow are “jet bifurcation”, “complex and strong shock structure” and “weak shock structure”.…”
Section: Introductionmentioning
confidence: 99%